(untitled) (Revista Contexto & Educação, 2025)
Through bibliographical research and data analysis, this article intends to critically analyze the guidelines of the national education plan 2014-2024, understanding guidelines as formulations that indicate the lines of action to be followed that are always expressed objectively, in a statement synthetic, and aim to define the general strategy and priorities of the Greater Plan. The aim here is not to analyze the goals and strategies of the national education plan, which will receive their own work, although connections will be made with these when essential for understanding the analysis. This work aims to see where the State has grown and where it failed in its proposal with the plan and provide suggestions and new measures as well as critically and politically point out the causes and consequences of any failures.